The Prohibition of Social E-Commerce on TikTok Shop: A Fiqh Examination Based on Sharia Compliance and Economic Justice - Naisabur, Nanang; Putra, Haris Maiza; Ahyani, Hisam; Novita, Dwi; Kurniati, Pat (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2024)
The prohobition of TikTok Shop in Indonesia has sparked debate over licensing and Shariah compliance. This article emphasizes the importance of using Shariah principles in social e-commerce at TikTok Shop. This research aims to analyze the rationale behind this from the perspective of fiqh and economic justice. This research uses a juridical-normative approach by analyzing relevant regulations using a descriptive-analytical method. Data was collected through a literature review, highlighting the importance of considering maslaha to maintain market stability and economic justice. The banning on TikTok Shop to ensure Shariah compliance to achieve economic justice. Government regulations or policies are beneficial, extending beyond mere prohibitions and restrictions. As commerce evolves with the expansion of digital platforms, it becomes imperative to establish clear regulations to accommodate this ongoing development.